2008
DOI: 10.1158/1535-7163.mct-08-0136
|View full text |Cite
|
Sign up to set email alerts
|

Pomegranate extract inhibits androgen-independent prostate cancer growth through a nuclear factor-κB-dependent mechanism

Abstract: Constitutive nuclear factor-KB (NF-KB) activation is observed in androgen-independent prostate cancer and represents a predictor for biochemical recurrence after radical prostatectomy. Dietary agents such as pomegranate extract (PE) have received increasing attention as potential agents to prevent the onset or progression of many malignancies, including prostate cancer. Here, we show that PE inhibited NF-KB and cell viability of prostate cancer cell lines in a dose-dependent fashion in vitro. Importantly, maxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
104
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 126 publications
(107 citation statements)
references
References 37 publications
3
104
0
Order By: Relevance
“…5). Our results are in line with evidence that points to a pathophysiologic role for NF-jB in PCa [48]. This factor was also associated with high expression of MMP9 and VEGF in PCa [49].…”
Section: Discussionsupporting
confidence: 92%
“…5). Our results are in line with evidence that points to a pathophysiologic role for NF-jB in PCa [48]. This factor was also associated with high expression of MMP9 and VEGF in PCa [49].…”
Section: Discussionsupporting
confidence: 92%
“…We have also shown that PE blocks NF-kB activity in prostate cancer models both in vitro and in vivo [14]. Inhibition of JNK by PE in immune cells has been demonstrated as well [15].…”
Section: Introductionmentioning
confidence: 57%
“…Over the past few years, consumer demand-based research on functional foods gave a basis for traditional using of pomegranate, which lead to an increase in number of scientific papers concerning pomegranate and its products with health-improving effects (Mehta & Lansky, 2004;Rettig et al, 2008;Turk et al, 2008;Alam et al, 2010;Dai et al, 2010;Jadeja et al, 2010;Park et al, 2010). The reports have focused on in vitro, ex vivo, and in vivo antioxidant actions, of pomegranate and its products, which are attributed to the chemical composition.…”
Section: Antioxidant Activitymentioning
confidence: 99%